Breeding superior banana/plantain hybrids - Lorenzen, J.H. (2012)
in this article, Musa species), is a major staple crop in Africa. Although it originated in Asia and was introduced to Africa long ago, it has become more important as a food security crop in its new home in Africa than in its region of origin. From its early domestication in Southeast Asia and the islands extending toward Australia, banana spread to Africa before recorded history. Archaeological evidence suggests that it reached Central Africa several millennia ago.